SISTEM INFORMASI KOMODITAS HASIL BUMI PADA GAMPONG BLANG DALAM GEUNTENG BERBASIS ANDROID - Amrullah; Rizki (Jurnal Elektro dan Informatika, 2020)
Today's technology has developed rapidly and has an enormous influence on the world of information technology. The emergence of various types of applications that can provide convenience and benefits in the activities of human life. Agricultural information is one of the important factors in the production process of farming. Agricultural empowerment so far has generally not yet significantly empowered farmers. So far, farmers have not gotten the information well. This research aims to design and create an Android-based commodity information system application. This application is expected to be useful for farmers as a medium of information and communication to increase agricultural productivity, thus the welfare of the farmers' community will be better.Keywords: android, agriculture, information technology